New and More Sustainable Processes for the Synthesis of Phenolics: 2-phenoxyethanol and hydroxytyrosol - Ziosi, Paolo <1987> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
The research work has dealt with the study of new catalytic processes for the synthesis of fine chemicals belonging to the class of phenolics, namely 2-phenoxyethanol and hydroxytyrosol. The two synthetic procedures investigated have the advantages of being much closer to the Green Chemistry principles than those currently used industrially. In both cases, the challenge was that of finding catalysts and methods which led to the production of less waste, and used less hazardous chemicals, safer solvents, and reusable heterogeneous catalysts. In the case of 2-phenoxyethanol, the process investigated involves the use of ethylene carbonate (EC) as the reactant for phenol O-hydroxyethylation, in place of ethylene oxide. Besides being a safer reactant, the major advantage of using EC in the new synthesis is the better selectivity to the desired product achieved. Moreover, the solid catalyst based on Na-mordenite was fully recyclable. The reaction mechanism and the effect of the Si/Al ratio in the mordenite were investigated. In the case of hydroxytyrosol, which is one of the most powerful natural antioxidants, a new synthetic procedure was investigated; in fact, the method currently employed, the hydrolysis of oleuropein, an ester extracted from the waste water processing of the olive, makes use of large amounts of organic solvents (hexane, ethyl acetate), and involves several expensive steps of purification. The synthesis procedure set up involves first the reaction between catechol and 2,2-dimethoxyacetaldehyde, followed by the one-pot reduction of the intermediate to give the desired product. Both steps were optimized, in terms of catalyst used, and of reaction conditions, that allowed to reach ca 70% yield in each step. The reaction mechanism was investigated and elucidated. During a 3-month period spent at the University of Valencia (with Prof. A. Corma’s group), a process for the production of diesel additives (2,5-bis(propoxymethyl)furan) from fructose has been investigated.